Indian mathematics : engaging with the world, from ancient to modern times - Joseph, George Gheverghese (Singapore : World Scientific, 2022)
Indian Mathematics gives a unique insight into the history of mathematics within a historical global context. It builds on research into the connection between mathematics and the world-wide advancement of economics and technology. Joseph draws out parallel developments in other cultures and carefully examines the transmission of mathematical ideas across geographical and cultural borders. Accessible to those who have an interest in the global history of mathematical ideas, for the historians, philosophers and sociologists of mathematics, it is a book not to be missed.
Chapter 1: Rewriting the history of India Chapter 2: Indian Mathematics in World Chapter 3: The Harappa - Vedic Nexus Chapter 4: From Zero to Infinity Chapter 5: Down to Earth and Reach for the Stars Chapter 6: Heralding the Golden Age Chapter 7: Riding the Crest of Wave Chapter 8: The 500 Year Climax Chapter 9: Navigating the Ocean of Mathematics Chapter 10: A Passage to Infinity Chapter 11: Indian Trignomentry Chapter 12: Outside the Sanskrit Tradition Chapter 13: Battle for the Mind
Gifted by NBHM through School of Science, IGNOU
Keywords: Mathematics -- India -- History; Mathematics -- India; Mathematics, Medieval